Development and psychometric testing of the patient participation in bedside handover survey. (27th July 2022) - Tobiano, Georgia; Marshall, Andrea P.; Gardiner, Therese; Jenkinson, Kim; Shapiro, Margaret; Ireland, Michael
Abstract: Introduction: When handover is conducted at the patient's bedside, active patient participation can be encouraged, which may improve the safety and quality of care. There is a need for valid and reliable tools to measure patient perceptions of participation in bedside handover, to ensure the rising number of implementation and improvement efforts are consistently and effectively evaluated. The aim of this study is to systematically develop and evaluate the psychometric properties of a self‐report survey to measure patients' perceptions of participation in bedside handover. Methods: In Phase 1, our team developed a conceptual framework and item pool ( n = 130). In Phase 2, content validity was assessed with four health consumers, four nurses and four researchers. Next, 10 current hospital inpatients tested the survey for end‐user satisfaction. In Phase 3, 326 inpatients completed the survey, allowing exploratory factor analysis, reliability analyses and convergent/divergent validity analyses to occur. Results: Phase 1 and 2 resulted in a 42‐item survey. In Phase 3, 321 surveys were available for analysis. Exploratory factor analysis revealed a three‐factor solution, with 24 items, which matched our conceptual framework. The three factors were: 'Conditions for patient participation in bedside handover', 'Level of patient participation in bedside handover' and 'Evaluation of patient participation in bedside handover'. There was strong evidence for factor reliability and validity. Additionally, the correlation between factors was strong. Conclusion: This study furthers our conceptual understanding by showing that nurse facilitating behaviours are a strong precursor for patient participation and perceived handover outcomes, justifying the need for nursing training. A robust survey has been developed to measure patient perceptions of participation in bedside handover, which can effectively evaluate this approach to care. Engaging consumers and nurses as research team members was invaluable in ensuring that the survey is acceptable for end‐users. Patient or Public Contribution: A health consumer and nurse partnered as members of the research team from study inception to dissemination.